Field notes from a catastrophe : man, nature, and climate change - Kolbert, Elizabeth; OverDrive, Inc. (2007)
Explores the issue of global warming from every angle, incorporating interviews with researchers and environmentalists, explaining the science and the studies, and presenting the personal tales of those who are being affected most.
Shishmaref, Alaska -- A warmer sky -- Under the glacier -- The butterfly and the toad -- The curse of Akkad -- Floating houses -- Business as usual -- The day after Kyoto -- Burlington, Vermont -- Man in the Anthropocene.
Reprint. Originally published: 2006. With a new afterword.
Includes bibliographical references (pages 207-218) and index.
Keywords: Global warming; Global temperature changes; Global environmental change; Global environmental change; Global temperature changes; Global warming; Electronic books